Business strategy for "kiddo" to be the leading family activity marketplace in indonesia - Tanuwidjaja, Analia; Dung Do, Anh (The Indonesian Journal of Business Administration, 2019)
Abstract. Kiddo is a marketplace brand from PT Kebanggaan Anak Indonesia, which was launched to the market in September 2018. This study aims to formulate creative business strategies so that Kiddo can achieve the company's short and long-term growth targets. The research methodology used is a quantitative method through questionnaires and qualitative methods through interviews with several stakeholders at Kiddo. Secondary data is also obtained from internal company data, books, articles, and others. The conceptual framework used in this study is external and internal analysis of the company. External analysis uses PEST Analysis and Porter’s Five Forces, while internal analysis uses VRIO models. The combination of external and internal analysis is also carried out using SWOT Analysis. The results of this analysis show a number of strengths and weaknesses of the company both from external and internal sides. The solution offered in this study is how Kiddo can win the market as the number one family activity marketplace in 2023. To better understand and execute the strategy into actions, a business model needs to be developed. For this research, Business Model Canvas will be used as a tool to make a structure of business plan with a clear guidance on how an organization creates, delivers, and captures value. To successfully execute the business strategy, an implementation plan is created through Marketing Mix 7Ps scheme.  Keywords: e-commerce, family, kids, marketplace, millennial parents, startups, technology